Resepsi Remaja terhadap Pornografi dalam Film Indonesia - Tri Hastuti Nur Rochimah; Fajar Junaedi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Soft core pornography became kind of pornographic on Indonesia movies. The rise of pornography led eventually chose enforce state laws Pornography, which is then invited a lot of controversy. Disagreements about pornography makes research on audience reception of the Indonesian film pornographic contents, as well as research on audience reception against pornography on movie of Mafia Insyaf and Rintihan Kuntilanak Perawan. Reception analysis obtained using the following results: the informants tend to be in a negotiating position by stating that the Mafia Insyaf and Rintihan Kuntilanak Perawan are films that can be categorized as soft core pornography.